Do multiparty elections improve human development in autocracies?. Issue 2 (17th February 2018) - Kim, Nam Kyu; Kroeger, Alex M.
ABSTRACT: Improvements in human development under democratic institutions are often attributed to electoral contestation. We evaluate the effect of multiparty contestation on infant mortality in the authoritarian context. Contrary to what extant scholarship argues, we find no evidence that multiparty elections in authoritarian regimes reduce infant mortality. Specifically, we show that electoral autocracies do not produce better infant mortality outcomes compared to closed autocracies holding no multiparty elections. We also demonstrate a non-monotonic effect of electoral competition on infant mortality: Infant mortality increases in levels of electoral contestation common in electoral authoritarian regimes and decreases only at levels of contestation that are nearly exclusive to democracies. Finally, we show that increases in infant mortality in electoral authoritarian regimes operate partially through increased political violence and reduced state capacity.